(untitled) (Bangladesh Journal of Botany, 2023)
Scanning Electron Microscopy (SEM) structures of leaf epidermis and spores of 9 species of Dryopteris Adans. from Shandong Province of China were studied. These species are: Dryopteris erythrosora (Eaton) O. Ktze., D. fuscipes C. Chr., D. tsoongii Ching, D. crassirhizoma Nakai and D. championii (Benth.) C. Chr., D. lijianxiuii X. J. Li (new species), D. shandongensis J. X. Li & F. Li, D. laoshanensis J. X. Li & S. T. Ma and D. parachinensis Ching & F. Z. Li. The study showed that the perispore ornamentation and submicroscopic structural characteristics of peripheral wall of leaf epidermal cells were stable within each species and have significant differences between species. It does not only provide evidences of submicroscopic structural characteristics for its morphological classification, but also provides a palynological basis for the classification and identification of new pteridophyte resources of Shandong area. A new Identification Key to 9 species of Dryopteris Adans. is prepared using both morphological and SEM characters of spores and leaf epidermis. Therefore, the submicroscopic structural characteristics of palynology and the leaf epidermis of the genus were of great significance in taxonomy. Bangladesh J. Bot. 51(4): 951-960, 2022 (December) Special